Porous Single-Crystalline Rare Earth Phosphates Monolith to Enhance Catalytic Activity and Durability - Wenting Li; Lingting Ye; Chaoyang Tu; Kui Xie (Molecules)
Rare earth phosphate (XPO4) is an extremely important rare earth compound. It can exhibit excellent activity and stability in catalytic applications by modifying its inherent properties. Porous single-crystalline (PSC) PrPO4 and SmPO4 with a large surface area consist of ordered lattices and disordered interconnected pores, resulting in activity similar to nanocrystals and stability resembling bulk crystals. Herein, we present a study in which centimeter-scale PSC PrPO4 and SmPO4 monoliths were developed and oxygen defects in the crystal lattice were stabilized using single-crystal nature to synergistically improve catalytic activity in the oxidative dehydrogenation of ethane (ODE). The surface structure of the oxygen vacancies with unsaturated coordination is favorable for the adsorption and activation of ethane. The PSC PrPO4 and SmPO4 monoliths showed favorable performance with ~51% conversion of C2H6 and ~19% yield of C2H4 at 600 °C, while also exhibiting superior long-term stability during the catalytic process over a period of 115 h. In the presented work, we investigate a practical method for development and application in single-crystalline porous rare earth phosphate materials.